Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, dan Motivasi Kerja Terhadap Kinerja Pegawai - Tolu, Angelique; Mamentu, Michael; Rumawas, Wehelmina (JURNAL ADMINISTRASI BISNIS (JAB), 2021)
Human resources are the most important assets that must be owned by an organization and must be considered in management, because they are the ones who work to make goals, innovate and achieve organizational goals. Good human resources will also reflect good performance. Understanding the importance of human resources today is one of the government's efforts to improve the quality of human resources themselves. The sample in this study were employees at Dinas Pertanian dan Peternakan of North Sulawesi Province. Â This study aims to analyze the influence of leadership style, work environment and work motivation on employee performance. This study used a questionnaire to obtain data from 125 respondents. Data were collected and analyzed using structural equation modeling (SEM) with the help of amos 24 software. The results showed that leadership style, work environment, and work motivation had a positive and significant effect on employee performance. The results showed that leadership style had a significant effect on employee performance, leadership style had a significant effect on work motivation, work environment had a significant effect on work motivation, work environment had a significant effect on work motivation. employee performance, and work motivation have a positive and significant effect on employee performance